Practical power of judgment by Neil MacCormick - Cern, Karolina M. (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The chief concern of the paper is to reconstruct the idea of the practical power of judgement, which in my view stands as a hidden philosophical background in Neil MacCormick’s writings in his post-positivist period. Firstly, I bring into light the source of and inspiration for his understanding of legal pluralism. Secondly, I analyse thoroughly the concept of norm-usage. Finally, drawing on my previous analyses, I argue that behind the legal pluralism and norm-usage there is a concept of judgmental-interpretative practice to be found which I reconstruct from MacCormick’s writings.